Management of Psoriatic Arthritis: Turkish League Against Rheumatism (TLAR) Expert Opinions - Gülcan GÜRER; Gürkan YILMAZ; İsmihan SUNAR and İlhan SEZER and Sumru ÖZEL and Erhan Ali ÖZDEMİREL and Hilal KOCABAŞ and Taciser KAYA and Ece KAPTANOĞLU and Ayhan KAMANLI and et al. (Archives of Rheumatology, 2018)
Objectives: This study aims to establish the first national treatment recommendations by the Turkish League Against Rheumatism (TLAR) for psoriatic arthritis (PsA) based on the current evidence. Materials and methods: A systematic literature review was performed regarding the management of PsA. The TLAR expert committee consisted of 13 rheumatologists and 12 physical medicine and rehabilitation specialists experienced in the treatment and care of patients with PsA from 22 centers. The TLAR recommendations were built on those of European League Against Rheumatism (EULAR) 2015. Levels of evidence and agreement were determined. Results: Recommendations included five overarching principles and 13 recommendations covering therapies for PsA, particularly focusing on musculoskeletal involvement. Level of agreement was greater than eight for each item. Conclusion: This is the first paper that summarizes the recommendations of TLAR as regards the treatment of PsA. We believe that this paper provides Turkish physicians dealing with PsA patients a practical guide in their routine clinical practice.